Both NaCl and H2O2 Long-Term Stresses Affect Basal Cytosolic Ca2+ Levels but Only NaCl Alters Cytosolic Ca2+ Signatures in Arabidopsis - Liu, Lulu; Jiang, Zhonghao; Zhang, Shu; Zhao, Hongyan; Yang, Weiguang; Siedow, James N.; Pei, Zhen-Ming (Frontiers in Plant Science, 2018)
Salinity is one of the formidable environmental factors that affect plant growth and development and constrain agricultural productivity. Experimentally imposed short-term NaCl treatment triggers a transient increase in cytosolic free Ca2+ concentration ([Ca2+]i) via Ca2+ influx across the plasma membrane. Salinity stress, as well as other stresses, induces the production of reactive oxygen species (ROS), such as H2O2. It is well established that short-term H2O2 treatment also triggers a transient increase in [Ca2+]i. However, whether and how long-term NaCl and H2O2 treatments affect the basal levels of [Ca2+]i as well as plant responses to additional NaCl and H2O2 stresses remain poorly understood. Using an aequorin-based Ca2+ imaging assay, we found that the long-term treatment of Arabidopsis seedlings with both moderate NaCl and H2O2 in the growth media reduced the basal [Ca2+]i levels. Interestingly, we found that the long-term treatment with NaCl, but not H2O2, affected the responses of plants to additional NaCl stress, and remarkably the roots displayed enhanced responses while the leaves showed reduced responses. These findings suggest that plants adapt to the long-term NaCl stress, while H2O2 might be an integrator of many stresses.